Performance of balance: General motor ability or specific adaptation of strategies? - Lippens, V.; Nagel, V.; Gottschall, J.; Peinke, J. (World Congress of Performance Analysis of Sport VIII, 2008)
The results are consistent with former studies (e.g., Lippens et al., 2007) and confirm the idea of functional integration of postural control under standing conditions (e.g., Stoffregen et al., 2007). Under sitting conditions the rowers have to obtain a certain level of performance before the suprapostural tasks facilitate the motor action (cf. Bloem et al., 2006). After a period of training under standing and sitting conditions as well, performance of balance was increased in the sitting, but not in the standing conditions. The new approach analyzing the variability in terms of drift and diffusion primarily confirms the results obtained on the basis of the standard deviation. A decrease in SD is for the most cases directly related to a smaller value for b0, i.e. the constant part of the diffusion coefficient. In addition, we found significant time effects for a0 in the sitting conditions. This can be explained with regard to the measurement setup. Repeating the experiment at another time, the test participants do usually not find exactly the same position they had for the first measurement on the balance board. Thus, the movement fluctuates around a slightly different, possibly less stable point. Accordingly, also the angular velocity may fluctuate around different fixed points that are not necessarily zero, resulting in an asymmetric and unstable or eventually instationary movement. Since the effect is observed for the whole group and not only for single participants, it can clearly be related to the setup. We conclude that a main effect for a0 serves as a kind of indicator for a modified setup and is helpful for the interpretation of time effects. Comparing standing with sitting, it seems that balance control of rowers is caused by different adaptations of strategies. More research under this new approach is needed to answer the question whether performance of balance is a general motor ability or a specific adaptation of strategies.